2011
DOI: 10.1038/ejcn.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Intake of antioxidants during pregnancy and the risk of allergies and asthma in the offspring

Abstract: Background/Objectives: The potential immune functions related to the damages induced by oxygen-free radicals suggest that antioxidants may have a role in the development of allergies. The objective was to investigate the association between maternal intake of antioxidants during pregnancy and the risk of asthma, rhinitis and eczema in 5-year-old children. Subjects/Methods: This study was on the basis of the Finnish Type 1 Diabetes Prediction and Prevention Nutrition Study, a population-based birth cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 28 publications
3
69
2
Order By: Relevance
“…Two previous studies of children's asthma at school age used FFQs to assess folate intake amounts from food and supplements, as in our study, during pregnancy (31,32). Nwaru and colleagues (31) studied children at age 5 years in Finland and found no association of total folate intake with asthma.…”
Section: Comparison With Other Studies and Potential Mechanismmentioning
confidence: 91%
“…Two previous studies of children's asthma at school age used FFQs to assess folate intake amounts from food and supplements, as in our study, during pregnancy (31,32). Nwaru and colleagues (31) studied children at age 5 years in Finland and found no association of total folate intake with asthma.…”
Section: Comparison With Other Studies and Potential Mechanismmentioning
confidence: 91%
“…One intervention and seven other studies were excluded [18][19][20][21][22][23][24][25]. The intervention study reported the outcomes of an intervention based on a supplement rather than food; seven cohort studies reported dietary intakes in terms of nutrients rather than foods.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies have reported maternal vitamin E intake not to be associated with childhood outcomes, although one highlighted their poor FFQ validity for vitamin E [21], another's FFQ was not validated for vitamin E [22] and the third only reported 1 year outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several have reported lower maternal dietary vitamin D intake during pregnancy to be associated with an increased risk of wheeze, asthma, eczema and atopic sensitisation in children up to the age of 7 years [2][3][4][5][6]; although maternal and/or umbilical cord blood 25-hydroxy-vitamin D 3 (25(OH)D 3 ) has been reported to be either not [7][8][9][10], adversely [11][12][13] or beneficially [14][15][16][17] associated with respiratory and/ or atopic outcomes up to the age of 9 years. Several studies have reported lower maternal dietary vitamin E intake during pregnancy to be either associated with an increased risk of wheezing at age 2 years [18,19] or not associated with asthma or atopic outcomes at age 1, 5 or 7 years [20][21][22].…”
Section: Introductionmentioning
confidence: 99%